The unequal multispecies entangled human-rat relation: How rodent control reveals colonial legacies in the lives of people of Lwandle/Nomzamo in Strand, Cape Town, South Africa - Clements, Thulasizwe (Social Anthropology, 2022)
Rat infestation torments people in poor communities. This is evident in the selling and circulation of agricultural pesticides that are repurposed as rodenticides in the informal settlements of Cape Town. The use of ‘street pesticides' has sparked debates about poor urban infrastructures that give rise to rodent infestations on one hand and concerns about animal welfare on the other. This research investigates the connection between the complex issue of rodent management and the inequalities faced by people living in Strand. Thinking about the ‘animal turn' in anthropology, this thesis considers the multifaceted issues around human-rat relations, poverty and race inequality in South Africa. The lack of service delivery and the subsequent proliferation of rats and other disease carrying pests negatively impacts the lives of people in poor communities. It is difficult to imagine that within this context the welfare of the rat emerges as a significant discourse in the Western Cape, especially in light of the ways in which political, cultural and socio-economic inequalities are reinscribed by colonial legacies that manifested themselves in the issue of rats and the many divides faced by poor people as highlighted in this research.